2021
DOI: 10.3390/ph14121281
|View full text |Cite
|
Sign up to set email alerts
|

Green-Synthesized Magnesium Hydroxide Nanoparticles Induced Osteoblastic Differentiation in Bone Co-Cultured Cells

Abstract: In this work, magnesium hydroxide NPs were synthesized using water (Mg(OH)2 NPs) or a rose hip (RH) extract (Mg(OH)2RH NPs) and tested for the bone cells’ effects in co-cultured osteoblastic and osteoclastic cells, using a Transwell® insert system, allowing reciprocal cell paracrine interactions. Behavior of each cell population was characterized for typical phenotype markers, at days 1 and 6. Cell cultures treated with osteogenic/osteoclastogenic inducers were used as positive control of cell differentiation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Such endeavours are still being pursued by scientists today. However, some prefer to integrate collagen with synthetic polymers such as polycaprolactone (PCL), polyglycolic acids (PLGAs) [ 209 ], polyvinyl alcohol [ 224 ], and glass bead particles [ 225 , 226 ] for various applications. For example, Xu et al (2022) explored the integration of synthetic polymer polycaprolactone (PCL) with rat tail collagen type I to reduce keratocyte differentiation and prevent fibrosis of the corneal stroma after injury [ 227 ].…”
Section: Current Insights and Conclusionmentioning
confidence: 99%
“…Such endeavours are still being pursued by scientists today. However, some prefer to integrate collagen with synthetic polymers such as polycaprolactone (PCL), polyglycolic acids (PLGAs) [ 209 ], polyvinyl alcohol [ 224 ], and glass bead particles [ 225 , 226 ] for various applications. For example, Xu et al (2022) explored the integration of synthetic polymer polycaprolactone (PCL) with rat tail collagen type I to reduce keratocyte differentiation and prevent fibrosis of the corneal stroma after injury [ 227 ].…”
Section: Current Insights and Conclusionmentioning
confidence: 99%
“…This was not the case of the extracts from anodized AZ31 and, in particular, the original alloy ( Figure 2 b). Higher extract dilutions (10% and 5%) did cause a stimulatory effect in TRAP activity, an enzyme beginning to be expressed early in the differentiation pathway and still present in the mature osteoclast [ 55 ], along with an up-regulation of the genes coding for TRAP (as expected, considering the higher enzyme activity) and for calcitonin receptors, a specific marker of these cells [ 54 , 56 ]. Nevertheless, it is worth noting that the expression of genes for the later markers C-src, with a key role in osteoclast bone resorbing activity, and Catk, a protease involved in the degradation of type I collagen in the bone matrix were not affected, probably suggested that the tested extracts did not induce the formation of fully mature resorbing osteoclasts compared to the control.…”
Section: Resultsmentioning
confidence: 92%
“…In control conditions, the mononuclear osteoclastic precursors of the peripheral blood were cultured in the presence of the factors MCSF and RANKL, known to induce osteoclastogenesis in vitro [ 54 ]. During osteoclastogenic differentiation, the high number of seeded mononuclear cells fused to form a much lower number of multinucleated functional osteoclasts at longer incubation times [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Here, we studied cellular behaviors upon treatment with 150 and 300 ug/mL, based on previous studies showing that 300-500 ug/mL of MgO nanoparticles kills 50% of BM-MSC cells and rosehip-functionalized MgO nanoparticles did not affect cell viability and proliferation in the concentration range of 1 to 100 ug/mL [35,36,44]. We showed that cells treated with Mg(OH) 2 -AS showed higher metabolic activity compared to cells treated with Mg(OH) 2 or AS alone.…”
Section: Discussionmentioning
confidence: 99%
“…This positive activity may be due to the release of Mg 2+ ions from Mg(OH) 2 -AS known to enhance osteogenic activity of BM-MSCs [46]. Spherical magnesium hydroxide mediated rose hip and Mg(OH) 2 with osteoblastic properties have been shown to be active on the MG-63 cell line [35]. Pinho et al postulated a beneficial impact of polyphenols in rosehip extract polyphenols.…”
Section: Discussionmentioning
confidence: 99%